The effects of environmental regulation and environmental protection investment on green technology innovation of enterprises in heavily polluting industries—based on threshold and mediation effect models - Yang, Bing; Zhao, Qi (Frontiers in Environmental Science, 2023)
Based on the green patent data and the corresponding enterprise data of A-share heavy polluting industry enterprises from 2010 to 2020, a comprehensive index of environmental regulation is constructed, and the system GMM estimation method, threshold effect test and intermediary effect model are used.The impact and mechanism of environmental regulation on enterprise green technology innovation are studied, and the heterogeneity of property rights is analysed. The following conclusions are drawn: (1) Environmental regulation presents a "U" shaped relationship of first suppressing and then promoting enterprise green technology innovation, and there is only a single threshold effect, and the "inflection point" is 2.7557; (2) There is an intermediary effect of environmental investment in the impact of environmental regulation on enterprise green technology creation, that is, environmental regulation affects enterprise green technology innovation by affecting the environmental protection investment behaviour of enterprises; (3) State-owned enterprises are more sensitive to environmental regulation, and environmental regulation has a greater impact on enterprise green technology innovation.